FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUASANWAJIB PAJAK PENGGUNA E-FILING: E-FILING - Imam M. Yusuf; Rusdi (Yayasan Kayyis Mulia Jaya, 2025)
This study aims to determine the effect of E-Filing System Quality, E-filing Information Quality, E-filing Timeliness on Taxpayer Satisfaction of E-filing users at KPP Pratama Pondok Aren with Respondents of this study are taxpayers who use e-filing. This data was collected using a questionnaire which was measured using a Likert scale. The population taken in this study was 9,476 e-filing user taxpayers recorded at KPP Pratama Pondok Aren, totaling 9,476 people and the sample from the calculation of the Slovin formula obtained a sample in this study of 100 respondents and processed using the SPSS 26 program. The results of the study showed that E-filing System Quality, E-filing Information Quality, E-filing Timeliness had a positive and significant effect on Taxpayer satisfaction of E-filing users at taxpayers in South Tangerang City. The coefficient of determination is 68.8%, the remaining 31.2% is influenced by other variables not examined in this study. Keywords: Quality of e-filing system, Quality of e-filing information, Timeliness of e-filing